Afrikataalleksikografie: Gister, vandag en môre - Prinsloo, D.J.; Taljard, Elsabé (Lexikos, 2017)
African Language Lexicography: Yesterday, Today and Tomorrow.This article aims to give a perspective on African language lexicography's response to developments in international lexicographic practice in relation to new trends and changes mainly brought about by the electronic era. The development of African language lexicography will be compared to that of mainly English paper and electronic dictionaries. Three periods of lexicographic development are distinguished. It will be argued that the overall picture for the development of African language lexicography compares less favourably to that of English and languages such as German and French. The focus will be on the availability of dictionaries, lexicographic quality, use of new computer technologies and the use of information sources made available by the information era. It will be concluded that in most instances African language lexicography is not keeping up with international developments in lexicography and that the number of challenges for these languages has increased. Finally a number of positive factors will be identified which could contribute to the improvement of the quality of dictionaries for African languages.